ОТКЛИК ГИДРОЭКОСИСТЕМЫ БАКАЛЬСКОЙ КОСЫ (КРЫМ) НА КЛИМАТИЧЕСКИЕ ИЗМЕНЕНИЯ: ДОННЫЕ ЦИАНОБАКТЕРИИ - Миходюк, О. С.; Герасименко, Л. М.; Шадрин, Н. В. (Marine Ecological Journal, 2023)
Response of hydroecological system of the Bakalskaya split (Crimea) on the climatic variability: the bottom cyanobacteria.